银屑病负担的多维概述. (19th July 2018) - Griffiths, C.E.M.; Jo, S.‐J.; Naldi, L.; Romiti, R.; Guevara‐Sangines, E.; Howe, T.; Pietri, G.; Gilloteau, I.; Richardson, C.; Tian, H.; Augustin, M.
Abstract : Linked Article:  Griffiths et al. Br J Dermatol 2018;179 :173–181